Оцінка посухостійкості Liriodendron tulipifera L. в умовах інтродукції у Правобережному Лісостепу України - Sulyga, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
Water regime of leaves is analysed and drought-resistance index of Liriodendron tulipifera L. are established on the ground of different evaluation methods of drought-resistance under conditions of introduction to Right-Bank of Forest-Steppe of Ukraine. Total water content, water deficit, relative leaf turgescence, water-holding capacity and ability of leaves to restore water content are established.